Enforcement at the EPA : high stakes and hard choices - Mintz, Joel A. (Austin : University of Texas Press, 2012)
The definitive history and assessment of the Environmental Protection Agency's role as America's environmental watchdog.
1. Introduction -- 2. "Where the Rubber Hits the Road and Everything Else Hits the Fan": A Brief Description of EPA's Enforcement Process and the Superfund Program -- 3. Heavy Seas before the Maelstrom: EPA Enforcement in the 1970s -- 4. Destruction, Confusion, Confrontation, and Disarray: EPA Enforcement and Congressional Oversight in the Gorsuch Era -- 5. "Away from the Brink"--But Not Out of the Woods: EPA Enforcement from 1983 to 1989 -- 6. Modest Progress and Renewed Suspicion: EPA Enforcement in the Bush I Administration -- 7. "Neither the Best of Times nor the Worst of Times": EPA Enforcement during the Clinton Administration -- 8. Suspicions, Schisms, and Partial Revival: EPA Enforcement during the Bush II Administration -- 9. Lessons Learned: Some Observations on Congressional Oversight, Organizational Structure, Management Approaches, and Career Staff Trends -- 10. Did Industry Capture EPA Enforcement? Captive Agency Theory and Its (Partial) Applicability -- 11. EPA Enforcement in the Context of Federal Civil Service Decline.
Includes bibliographical references and index.
Keywords: UNITED STATES -- ENVIRONMENTAL PROTECTION AGENCY